Risk Management in Engineering and Construction: A Case Study in Design-Build Projects in Vietnam - Nguyen, P. T.; Nguyen, P. C. (Engineering, Technology & Applied Science Research, 2020)
The constant demand for construction in developing countries like Vietnam causes more and more challenges and difficulties to Project Management Units (PMUs) in carrying projects to completion on schedule, with quality assurance and fewer costs. In order to do this, PMUs need to have better and tighter management tools and forms. However, in order to minimize risks during project implementation, the binding terms in contracts are also becoming stricter with more and more new forms of contracts. One of them is the design-build (DB) contract form. This paper presents the critical risk factors for design-build projects in the construction industry. Good identification and management of these risk factors will help projects succeed and will increase the confidence of owners and contractors who seek to use the design-build form.